Effects of Mobile Technology on Human Relationships - Mohammed M. Elsobeihi; Samy S. Abu Naser (International Journal of Engineering and Information Systems (IJEAIS), 2017)
Technology plays an essential and important role in industrial and developing countries. Technology has affected almost all walk of human life such as education and social life. It has drastically changed the cultural norms and behavior of individuals. This study aims to find out the relation between mobile technology and its effects on face- to- face communications at Al-Azhar University in Gaza. The major objectives of this research are to examine the relationship between mobile technology use and the ability of people to communicate face- to- face and to find out whether mobile usage is weakening the quantity and quality of face- to- face interactions. This study found out that the use of mobile technology have negative impact on both the quality and the quantity of face- to- face communications. The study concludes that mobile use by individuals has reduced the time they spend engaging in face- to- face communications with each other because of the time spent on the mobile.
Keywords: 330; Technology; impact; mobile; communications